Hubungan Profil D-dimer Terhadap Tingkat Keparahan Stroke Iskemik Teritori di Rumah Sakit Umum Daerah Banten - Damayanti, Marshavina; Rusmana, Ahmad Irwan; Utami, Louisa Ivana (Tirtayasa Medical Journal, 2024)
Ischemic stroke become the most common cause of mortality and disability for elderly in Indonesia. Territorial ischemic stroke are often associated with the presence of blood clots that clog blood vessels in the brain. There were somehow association in different studies between increased levels of d-dimer as a fibrinolysis factor and the severity of territorial ischemic stroke which evaluated by using National Institutes of Health Stroke Scale (NIHSS) scores. This study aimed to analyze the association of d-dimer profile to the severity of territorial ischemic stroke. A Cross sectional study was conducted by taking secondary data retrospectively through medical records at the Medical Record and Radiolgy Installation at Banten Regional Public Hospital. D-dimer profile was categorized with a cutoff point 1000 ng/mL and NIHSS score was categorized with a cutoff point 10. The statistical analysis test used in this study was Fischer Exact Test. Forty-One of territorial ischemic stroke patients data were included in this study. Territorial ischemic stroke patients were mostly in the age group of 51—60 years with 16 patients (39%), males with 22 patients (53,7%), education in elementary school with 14 patients (34,1%), and territorial ischemic at left brain hemisphere precisely on frontal lobe with 14 patients (34,1%), temporal lobe with 15 patients (36,6%), and parietal lobe with 15 patients (36,6%). There was statistically significant association (p = 0,016) between the d-dimer profile and severity of territorial ischemic stroke (OR 9,6; 95% CI (1,5—60,6)). Early abnormal d-dimer levels on admission cause worsening of the condition in patients with territorial ischemic stroke based on NIHSS scores.